El hijo del elefante - Kipling, Rudyard, 1865-1936.; Mogensen, Jan (Mexico, D.F. : Consejo Nacional para la Cultura y las Artes, 1990)
Because of his curiosity about what the crocodile has for dinner, the elepant's child and all elephants thereafter have long trunks.